The Relative Influence of Parental Attachment, Peer Attachment, School Attachment, and School Alienation on Delinquency among High School Students in Turkey. Issue 7 (2nd July 2016) - Yuksek, Durmus A.; Solakoglu, Ozgur
ABSTRACT: Although numerous studies have confirmed the relationship between social bonds to pro-social others and delinquency in Western countries, research focusing on the same relationship in non-Western countries is scarce. This study contributes to the existing body of knowledge by examining the relationship between social bonds to pro-social others and several types of delinquency among high school students in Turkey. Results showed that the extent of an adolescent's social bonds with his/her parents, peers, and schools had significant and diverging effects on delinquency. We also found bonds to parents and peers to have moderating effects on how school bonds affect delinquency.